The Ummah narrative in Indonesian politics: between emotional mobilization and the rationality of democracy and its impact - Situmorang, Jubair; Samad Umarama; Abu Sahman; Asniah (Indonesian Journal of Islam and Muslim Societies, 2025)
This study analyzes the phenomenon of ummah narrative in contemporary Indonesian politics and its impact on the quality of democracy. Employing qualitative research methods with case studies on the 2019 Presidential Election, the 2024 Presidential Election, and the 212 Movement/Aksi Bela Islam, this study explores the mechanism of emotional mobilization through the ummah narrative and its influence on the rationality of democracy. The study’s findings reveal that the ummah narrative operates through the construction of a collective identity, utilizing religious symbolism and majority-minority sentiments. This emotional mobilization mechanism is supported by factors such as political polarization, the use of digital media, charismatic leadership, and socio-economic contexts. The dominance of the ummah narrative on the rationality of democracy can be seen in the declining quality of public deliberation, the reduction of political pluralism, and the fragmentation of social cohesion. This research contributes to the understanding of identity politics in Indonesia and its implications for democratic consolidation. The novelty of the study lies in its comprehensive analysis, which combines the perspectives of emotional mobilisation theory, deliberative democracy, and identity politics in the context of the narrative of the Indonesian ummah. The results of this research are relevant for developing a strategy to strengthen democracy that is more inclusive and rational in Indonesia. Penelitian ini menganalisis fenomena narasi keummatan dalam politik Indonesia kontemporer dan dampaknya terhadap kualitas demokrasi. Menggunakan metode penelitian kualitatif dengan studi kasus pada Pemilu Presiden 2019, Pemilu Presiden 2024, dan Gerakan 212/Aksi Bela Islam, penelitian ini mengeksplorasi mekanisme mobilisasi emosional melalui narasi keummatan dan pengaruhnya terhadap rasionalitas demokrasi. Temuan penelitian menunjukkan bahwa narasi keummatan bekerja melalui konstruksi identitas kolektif yang memanfaatkan simbolisme religius dan sentimen mayoritas-minoritas. Mekanisme mobilisasi emosional ini didukung oleh faktor-faktor seperti polarisasi politik, penggunaan media digital, kepemimpinan karismatik, dan konteks sosio-ekonomi. Dampak dominasi narasi keummatan terhadap rasionalitas demokrasi terlihat pada menurunnya kualitas deliberasi publik, tereduksinya pluralisme politik, dan terfragmentasinya kohesi sosial. Penelitian ini memberikan kontribusi pada pemahaman tentang politik identitas di Indonesia dan implikasinya bagi konsolidasi demokrasi. Kebaruan penelitian terletak pada analisis komprehensif yang menggabungkan perspektif teori mobilisasi emosional, demokrasi deliberatif, dan politik identitas dalam konteks narasi keummatan Indonesia. Hasil penelitian ini relevan bagi pengembangan strategi penguatan demokrasi yang lebih inklusif dan rasional di Indonesia.